Sink or break: Oil increases resistance of phytoplankton aggregates to fragmentation - Kai Ziervogel; Julia A. Sweet; Yixuan Song; Laura Bretherton; Matthew J. Rau; Antonietta Quigg; Uta Passow (Limnology and Oceanography Letters)
Abstract Fragmentation of marine snow affects the downward flux of organic matter, and other aggregate‐associated compounds such as oil. Using phytoplankton aggregates, we demonstrate that marine snow with oil, termed marine oil snow, had a higher resistance to fragmentation compared to marine snow without oil when exposed to turbulence ex situ. At moderate shear levels, typical of the ocean mixed layer, 17% of marine snow without oil broke, whereas 63% of marine snow fragmented at intermediate shear. In contrast, only 17% and 33% of marine oil snow fragmented at the intermediate and highest shear levels, respectively. Our results suggest that oil increases the cohesion and stability of aggregates making them less susceptible to breaking. This work contributes toward explaining the exceptional oil sedimentation event following the 2010 spill in Gulf of Mexico. It also enhances our understanding of the factors that determine the probability of sinking aggregates to fragment.